Recovery pattern of cyclone-affected coconut palms in littoral sandy soils of Orissa-Part II - G.C. Acharya (International Coconut Community, 2007)
The experiment to study the recovery pattern of cyclone affected palms cv. Sakhigopal Local was carried out in an ongoing fertilizer trial with three levels each of N (500, 1000 and 1500 g N/palm/ year), P (250, 500 and 750 g P2O5/palm/year) and K (750, 1250 and 1750 g of K2O/palm/year) at Coconut Research Station under Orissa University of Agriculture and Technology. The study indicated that the manuring practices comprising higher doses of N, P and K were most effective, nitrogen in particular in bringing out a gradual improvement in the reproductive characters of the coconut palms affected by the super cyclone, 1999. Enhanced nitrogen application (1000g/palm/year) induced production of more number of inflorescences, more of female flowers and increased yield per palm during initial years of damage irrespective of the degree of damage suffered by the adult palms in the littoral sandy soils of Orissa. The nut yield per palm per year exhibited significant increase at N levels of 500 to 1000 g per palm per year during 2001-02 to 2003-04 under damage category I. The importance of this level of nitrogen was marked during 2000-01 to 2002-03 in damage category II and during 2000-01 to 2001-02 in damage category III. The 1500 g nitrogen per palm per year did not show any significant change over 1000 g as regards to the nut yield per palm.